The potential of Trichoderma in the sustainable development of agriculture - Barbarita Companioni González (Biotecnología Vegetal, 2019)
The sustainable production of food without affecting the environment is nowadays a society challenge that requires transforming the conventional systems of agricultural exploitation to agroecological in the productive forms. In this sense, the use of microorganisms for pests and diseases control constitutes a viable alternative to achieve significant increases yields, quality of the crops and reduce the negative impact of agrochemicals on the environment. Trichoderma is considered one of the most common fungal phytopathogenic antagonists in modern sustainable agriculture. This paper summarizes some theoretical and practical aspects of the multiple benefits provided by the species of Trichoderma spp. Therefore, this has made possible the development of formulation through plant biotechnology and its application in the development of sustainable agriculture.